2000
DOI: 10.1091/mbc.11.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of ATP-dependent Movement of Endocytic Vesicles Along Microtubules In Vitro: An Oscillatory Bidirectional Process

Abstract: We have previously used the asialoglycoprotein receptor system to elucidate the pathway of hepatocytic processing of ligands such as asialoorosomucoid (ASOR). These studies suggested that endocytic vesicles bind to and travel along microtubules under the control of molecular motors such as cytoplasmic dynein. We now report reconstitution of this process in vitro with the use of a microscope assay to observe the interaction of early endocytic vesicles containing fluorescent ASOR with fluorescent microtubules. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 38 publications
(55 reference statements)
4
127
0
4
Order By: Relevance
“…This in vitro system has permitted identification of native endogenous proteins that are required for microtubulebased processing of endocytic vesicles. Using these tools, we found that plus-end motility of early endocytic vesicles from rat liver was mediated by the conventional kinesin Kif5B (standardized nomenclature kinesin-1) (Miki et al, 2003(Miki et al, , 2005Lawrence et al, 2004), and minus-end motility was mediated by Kifc2 (standardized nomenclature kinesin-14B) (Bananis et al, , 2003(Bananis et al, , 2004Murray et al, 2000). Whereas Kifc2 was initially described as a brain-specific minus-enddirected kinesin Saito et al, 1997), our studies showed that it was highly associated with these vesicles prepared from rat liver (Bananis et al, 2003).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…This in vitro system has permitted identification of native endogenous proteins that are required for microtubulebased processing of endocytic vesicles. Using these tools, we found that plus-end motility of early endocytic vesicles from rat liver was mediated by the conventional kinesin Kif5B (standardized nomenclature kinesin-1) (Miki et al, 2003(Miki et al, , 2005Lawrence et al, 2004), and minus-end motility was mediated by Kifc2 (standardized nomenclature kinesin-14B) (Bananis et al, , 2003(Bananis et al, , 2004Murray et al, 2000). Whereas Kifc2 was initially described as a brain-specific minus-enddirected kinesin Saito et al, 1997), our studies showed that it was highly associated with these vesicles prepared from rat liver (Bananis et al, 2003).…”
Section: Introductionmentioning
confidence: 80%
“…Texas Red-labeled early endocytic vesicles were prepared from mouse or rat liver as described previously (Bananis et al, , 2003Murray et al, 2000). In brief, livers were harvested 5 min after portal venous injection of 50 g of Texas Red-labeled ASOR.…”
Section: Endosome Isolation and In Vitro Motility Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…The complementary roles played by the actin cytoskeleton and microtubule network in the endocytic pathway (van Deurs et al, 1995;Durrbach et al, 1996;Maples et al, 1997;Murray et al, 2000) suggest that endosomes contain proteins allowing for movement on both types of cytoskeletal network. Small GTPases of the rab family have been suggested to be required for endosome motility and recycling.…”
Section: Discussionmentioning
confidence: 99%